Analysis of electromagnetic waves using the explicit group WE-FDTD method - Md Nusi, Noraini; Othman, Mohamed; Suleiman, Mohamed; Ismail, Fudziah (WSEAS Press, 2013)
In this paper, a new explicit group method for scalar wave finite difference time domain (WE-FDTD) is presented to simulate the propagation of two dimensional electromagnetic waves. This method is derived using the implicit Crank-Nicolson finite difference approximation that can be easily converted to explicit form. It is found that the presented method has no longer restricted by stability conditions, improves the accuracy of the conventional finite difference time domain (FDTD) method and provides significant savings in the computational time. Some numerical experiments are included to demonstrate the performance of the presented explicit group method.